Radical environmental resistance : love, rage and hope in an era of climate and biodiversity breakdown - Alberro, Heather (Emerald points., 2023)
Acknowledging mounting socioeconomic inequality, a climate system in disarray, and a collapse of biodiversity that now threatens the very viability of life on earth for both present and future generations, Radical Environmental Resistance demystifies activists' ecological worldviews, their tactical motivations, and their diagnostic and prognostic framings. Providing a succinct overview of key aspects of contemporary radical environmental movements, Heather Alberro offers a brief yet in-depth look into the poorly understood aims and motivations of radical environmental activists as increasingly salient actors within global environmental politics. Drawing on semi-structured interviews with activists from a range of environmental groups as well as analysis of activist websites and print materials, chapters feature a critical discussion of the ethics and salience of radical tactics and of attempts by state, media and corporate actors to criminalize and delegitimize environmental activism. Will mainstream policy and government approaches to addressing climate and biodiversity crises amount to too little, too late? At what point, if ever, do desperate times legitimize desperate actions? Exploring the role of direct action within times of severe social and ecological upheaval, Radical Environmental Resistance evokes the rich, diverse world that radical environmental activists and indigenous environmental protectors are fighting for.